Domestic perspectives on contemporary democracy - Nardulli, Peter F. (Democracy, free enterprise, and the rule of law., 2008)
In looking at the remarkable proliferation of democracies since 1974, this volume offers important insight into the challenges and opportunities that democracy faces in the twenty-first century. Distinguished contributors detail the contemporary threats to democracy emanating from internal sources such as tensions arising over technology and its uses; ethnic, religious, and racial distinctions; and disparate access to resources, education, and employment. _x000B__x000B_Contributors are W. Lance Bennett, Bruce Bimber, Jon Fraenkel, Brian J. Gaines, Bernard Grofman, Wayne V. McIntosh, Peter F. Nardulli, Mark Q. Sawyer, Stephen Simon, Paul M. Sniderman, and Jack Snyder._x000B_